PRINCIPAL PERSONALITY COMPETENCY: META ANALYSIS AND SYSTEMIC REVIEW - Rifaudin, Ahmad; Tarihoran, Naf’an; Nugraha, Enung (Yayasan Education and Social Center, 2025)
This research aims to explore the influence of madrasa head personality competence on the quality of education through meta-analysis and systematic review. The personality competencies of madrasah heads, which include aspects of empathy, communication and leadership, have been proven to have a significant impact on teacher performance, work climate and teaching motivation. This study analyzes various research conducted between 2020 and 2024, which indicates that madrasa heads with good personality competencies can create an environment that supports effective learning. Apart from that, madrasa heads who are able to manage human resources and conflicts within the school can also improve student achievement. The results of this research show the importance of developing the personality competencies of madrasa heads to improve the quality of education and management of madrasas as a whole. This research contributes to a deeper understanding of the important role of personality competence in educational leadership in madrasas.